USULAN PENGEMBANGAN BISNIS RURAL LOGISTICS E-COMMERCE DI PT. POS INDONESIA (PERSERO) - Gunawan, Andri (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Rural areas have a very potential market to be developed by the logistics company industry, because they have a significant demand for goods in rural areas where the internet has become popular in rural communities. This phenomenon is an opportunity for PT. Pos Indonesia to build a logistics service business by forming a logistics integration division to manage all logistics business activities. But in reality the performance of the logistics business income of PT. Pos Indonesia is still very small. One of the causes is the non-optimal performance of the logistics business of PT. Pos Indonesia is not yet clear the concept of business to be carried out. In this research, the proposal to develop a rural logistics e-commerce business is carried out thoroughly based on the main reference of Dong Haoping (2010), namely in developing rural logistics e-commerce business by using the postal network owned to rural areas. The results of the proposed new business concept of PT. Pos Indonesia is developing a rural logistic business model that is followed by an e-commerce business platform where PT. Pos Indonesia acts as a provider of rural logistics services. With the availability of rural logitics e-commerce services, it is expected to facilitate the reach of rural and urban communities to obtain their respective basic needs with price stability and availability of goods that can be controlled, while improving company.